2021
DOI: 10.1038/s41598-021-03500-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and tissue localization of zebrafish homologs of the human ABCB1 multidrug transporter

Abstract: Capillary endothelial cells of the human blood–brain barrier (BBB) express high levels of P-glycoprotein (P-gp, encoded by ABCB1) and ABCG2 (encoded by ABCG2). However, little information is available regarding ATP-binding cassette transporters expressed at the zebrafish BBB, which has emerged as a potential model system. We report the characterization and tissue localization of two genes that are similar to ABCB1, zebrafish abcb4 and abcb5. When stably expressed in HEK293 cells, both Abcb4 and Abcb5 conferred… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…Our interpretation of behavioral responses to ivermectin in zebrafish is also in line with literature focused on neurotoxicity risk dependent on the absorption-extrusion activity of the drug from the gastrointestinal tract and blood brain-barrier, which is regulated by P-glycoprotein (P-gp), environment-susceptible genes coding for Pgp, such as ABCB1 (also known as multi-drug resistant express the ABCB1 gene, they do express the homologs ABCB4 and ABCB5, and ABCB4 has indeed been demonstrated to phenocopy P-gp function in zebrafish [36].) Genetic mutations in this context may therefore further increase the risk of penetration of ivermectin across the blood brain barrier, e.g.…”
Section: Discussionsupporting
confidence: 69%
“…Our interpretation of behavioral responses to ivermectin in zebrafish is also in line with literature focused on neurotoxicity risk dependent on the absorption-extrusion activity of the drug from the gastrointestinal tract and blood brain-barrier, which is regulated by P-glycoprotein (P-gp), environment-susceptible genes coding for Pgp, such as ABCB1 (also known as multi-drug resistant express the ABCB1 gene, they do express the homologs ABCB4 and ABCB5, and ABCB4 has indeed been demonstrated to phenocopy P-gp function in zebrafish [36].) Genetic mutations in this context may therefore further increase the risk of penetration of ivermectin across the blood brain barrier, e.g.…”
Section: Discussionsupporting
confidence: 69%
“…Generation and validation of a knockout model of the zebra sh homolog of the human ABCB1 Two orthologs of human ABCB1, abcb4 and abcb5, are found in the zebra sh, of which abcb4 is functionally similar to human ABCB1 [16,17]. To elucidate the in vivo roles of zebra sh abcb4 in more details, we generated an abcb4-mutated zebra sh line using CRISPR/Cas9 genome editing technology.…”
Section: Resultsmentioning
confidence: 99%
“…In zebra sh, Abcb4 and Abcb5 are both associated with e ux transport activities. However, zebra sh Abcb4 protein has a highly overlapping substrate speci city pro le with human Pgp [17]. In addition, previous studies based on morpholino knockdown found that zebra sh Abcb4 transports several uorescent Pgp substrates in embryos [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations